Medical Use and Misuse of Prescription Opioids in the US Adult Population: 2016–2017 - Griesler, Pamela C. (Am J Public Health, 2019)
Objectives. To characterize prescription opioid medical users and misusers among US adults. Methods. We used the 2016–2017 National Surveys on Drug Use and Health to compare medical prescription opioid users with misusers without prescriptions, misusers of own prescriptions, and misusers with both types of misuse. Multinomial logistic regressions identified substance use characteristics and mental and physical health characteristics that distinguished the groups. Results. Among prescription opioid users, 12% were misusers; 58% of misusers misused their own prescriptions. Misusers had higher rates of substance use than did medical users. Compared with with-prescription-only misusers, without-and-with-prescription misusers and without-prescription-only misusers had higher rates of marijuana use and benzodiazepine misuse; without-and-with-prescription misusers had higher rates of heroin use. Compared with without-prescription-only misusers, without-and-with-prescription and with-prescription-only misusers had higher rates of prescription opioid use disorder. Most misusers, especially with-prescription-only misusers, used prescription opioids to relieve pain. Misusers were more likely to be depressed than medical users. Conclusions. Prescription opioid misusers who misused both their own prescriptions and prescription opioid drugs not prescribed to them may be most at risk for overdose. Prescription opioid misuse is a polysubstance use problem.